REMISSION IS A CHARACTERISTIC FEATURE OF ACUTE LEUKEMIA IN YOUNG CHILDREN - Mamadaminov Abdullo Azimjon ugli (Journal of new century innovations, 2023)
Abstract: Leukemia in children during the first months of life is an extremely rare pathology. Hostile leukemia is detected, as a rule, soon after birth, is acute, according to literature data, children die in the first 3-4, less often 6 weeks. We watched a child who was growing up to 3.5 months, developing normally and not suffering from anything, the fatal outcome came at 5.5 months from leukemia. The child is 3.5 months old, was admitted to the Shofirkan regional hospital, the children's department with a diagnosis of Acute respiratory viral infection. Sop. Umbilical and inguinal herd.